Oncogenic role and therapeutic target of transient receptor potential melastatin 7 channel in malignancy. (October 2014) - Zhou, Weiqiang; Guo, Shanchun; Xiong, Zhigang; Liu, Mingli
<x xml:space="preserve">Abstract</x> Introduction: The transient receptor potential (TRP) family is a superfamily of cation channels which regulates many features of malignant cancers, such as lack of differentiation, increased migratory and invasive phenotype and chemoresistance. The TRP cation channel, TRPM7 (subfamily M, member 7), is a ubiquitous, Ca2+ and Mg2+-permeant ion channel that is unique in that it is an ion channel and a serine/threonine kinase. TRPM7 has been associated with cell proliferation, survival and development and thus correlated with growth and progression of several types of tumor cells, including breast cancer, gastric cancer, head and neck cancer, nasopharyngeal carcinoma, pancreatic cancer, prostate cancer, retinoblastoma and leukemia. Increased TRPM7 expression in human breast and pancreatic cancer tissues also correlates with clinicopathological parameters, such as tumor grade, the Ki-67 proliferation index and patient survival. Areas covered: In this review, we focus on recent advancements in knowledge of aberrant TRPM7 channel function and its contribution to tumor progression and angiogenesis. This includes crosstalk between multiple signaling pathways. The role of TRPM7 in tumor development, particularly in regard to its channel function mediating both Ca2+ and Mg2+ influx as well as its kinase activity is also addressed. In addition, we will discuss its role in the stem cell and cancer stem cell, as well as its potential as tumor drug target. Expert opinion: Better understanding of the structure, function and regulation of TRPM7 channel, as well as its complex crosstalk with other oncogenic signals in tumor cells will be essential to ensure rational use of treatment and development of new combinatory therapeutic possibilities.